Optimization of the Internal Quality Assurance System (SPMI) at the Army Polytechnic (Poltekad) through the Development of Organizations and Tasks (Orgas) of the Quality Assurance Agency (LPM) - Suherli, Suherli (Dinasti International Journal of Management Science, 2025)
Internal Quality Assurance System (SPMI) is a fundamental aspect in maintaining and improving the quality of higher education. The Army Polytechnic (Poltekad) as a higher education institution within the Indonesian Army has a great responsibility in implementing SPMI. This study aims to analyze and optimize SPMI at Poltekad through the development of the organization and duties of the Quality Assurance Institution (LPM). A qualitative approach was used with the methods of document study, interviews, and observation. The results of the study indicate the need to improve the organization and duties of LPM structurally, including increasing the rank of the Head of LPM and increasing the number of personnel. Optimization of SPMI at Poltekad can be achieved through the development of LPM, which will contribute to improving the quality of education and meeting quality standards. This study emphasizes the importance of strengthening LPM in the context of quality assurance of higher education in Indonesia.